2004
DOI: 10.3201/eid1001.030144
|View full text |Cite
|
Sign up to set email alerts
|

Panton-Valentine Leukocidin and Staphyloccoccal Skin Infections in Schoolchildren1

Abstract: The Panton-Valentine leukocidin is associated with staphylococcal skin and pulmonary infections. We describe a school outbreak of skin infections and the public health response to it. Nasal carriage of a Panton-Valentine leukocidin–positive Staphylococcus aureus clone was detected only in previously ill classmates and their family members.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
53
0
12

Year Published

2004
2004
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(67 citation statements)
references
References 10 publications
1
53
0
12
Order By: Relevance
“…The Oxford Staphylococcus and phage type 80/81 MSSA strains were main pandemic clones, harboring PVL genes, in the 1950s and 1960s (Robinson et al, 2005;Kearns et al, 2006). Recently, in some parts of Europe, PVL-positive MSSA strains have been associated with severe skin infections (Boubaker et al, 2004;Lesens et al, 2007;Wiese-Posselt et al, 2007;Tinelli et al, 2009). …”
Section: Introductionmentioning
confidence: 99%
“…The Oxford Staphylococcus and phage type 80/81 MSSA strains were main pandemic clones, harboring PVL genes, in the 1950s and 1960s (Robinson et al, 2005;Kearns et al, 2006). Recently, in some parts of Europe, PVL-positive MSSA strains have been associated with severe skin infections (Boubaker et al, 2004;Lesens et al, 2007;Wiese-Posselt et al, 2007;Tinelli et al, 2009). …”
Section: Introductionmentioning
confidence: 99%
“…Studies by Boubaker et al ( 28 ) and Osterlund et al ( 9 ) have shown that household members of MRSA–colonized persons are at increased risk for becoming colonized. Our data support the hypothesis that transmission of MRSA from carriers to non-colonized household members is a risk factor for disease acquisition.…”
Section: Discussionmentioning
confidence: 99%
“…4 Si bien los genes que codifican la resistencia a meticilina de las cepas hospitalarias y comunitarias son los mismos, el cassette cromosómico estafilocócico en el cual están integrados esos genes es diferente, lo que indica que las cepas de la comunidad no representan una diseminación de las cepas hospitalarias. 12,13 Asimismo, una citotoxina llamada leucocidina Panton-Valentine (PVL) presente en las cepas SAMR-C y en algunas SA meticilino sensibles (SAMS) se asoció a IPPB, 4,14 invasividad, osteomielitis, neumonía necrotizante y mal pronóstico. 4,[14][15][16][17][18] Sin embargo, recientemente, se ha discutido su rol como determinante de virulencia.…”
unclassified
“…12,13 Asimismo, una citotoxina llamada leucocidina Panton-Valentine (PVL) presente en las cepas SAMR-C y en algunas SA meticilino sensibles (SAMS) se asoció a IPPB, 4,14 invasividad, osteomielitis, neumonía necrotizante y mal pronóstico. 4,[14][15][16][17][18] Sin embargo, recientemente, se ha discutido su rol como determinante de virulencia. 19 Los objetivos del presente estudio fueron estimar la tasa de hospitalización de la infección por SAMR-C, describir las características clínico-epidemiológicas y microbiológicas de los pacientes, y analizar los factores de riesgo de letalidad en centros seleccionados que representaban diferentes áreas del país.…”
unclassified